2010
DOI: 10.1007/s10660-010-9044-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between website quality, trust and price premiums at online auctions

Abstract: This study measures the value of website quality in terms of its impact on trust, intention to transact and price premiums. Prior research on online auctions has focused on the use of reputation systems for building trust in online auction vendors and subsequently to generate price premiums. This study examines the extent to which trust can be induced by improving the quality of online auction listings. A survey of 701 eBay users is conducted which compares the price premiums of two nearly identical online auc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
0
16

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(107 citation statements)
references
References 94 publications
(159 reference statements)
2
89
0
16
Order By: Relevance
“…In fact, even perceived quality positively affects trust [48]. Trust indicates the degree of perceived reliability or confidence that consumers have toward a person, event, object or process.…”
Section: Green Perceived Qualitymentioning
confidence: 99%
“…In fact, even perceived quality positively affects trust [48]. Trust indicates the degree of perceived reliability or confidence that consumers have toward a person, event, object or process.…”
Section: Green Perceived Qualitymentioning
confidence: 99%
“…Parasuraman, A., Zeithaml, V., & Berry, L. (1996. The behavioral consequences of service quality.Journal of Marketing,60,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Rebekah Pure (MA, University of California, Santa Barbara) is a doctoral candidate in the Department of Communication at the University of California at Santa Barbara, and a survey specialist at NORC at the University of Chicago. Her research focuses on the legal implications of information technology, and specifically on privacy and trust in the social media environment.…”
mentioning
confidence: 99%
“…In addition, a growing body of research has explored the relationship between product quality and purchase intention in the context of ecommerce, and found that ratings (e.g., [15,20,27,74,89]), website quality [41], and the perceived credibility of electronic word-of-mouth messages [17] all positively impact purchase decisions. Moreover, the perceived valence and credibility of product recommendations have been shown to have a significant impact on purchase intention, across a variety of consumer goods [38].…”
mentioning
confidence: 99%
“…When website quality is affirmed, an attitude of credibility/trust toward the information/source on the website can be established. [33]. Further, a well-designed website interface induces more positive emotional and cognitive evaluations of crowdfunding projects.…”
Section: Activating Internal Reactions: Stimulus Of Environmental Cuesmentioning
confidence: 99%